2008
DOI: 10.1002/glia.20737
|View full text |Cite
|
Sign up to set email alerts
|

Hypoosmotic swelling affects zinc homeostasis in cultured rat astrocytes

Abstract: Astrocyte swelling is observed in different types of brain injury including hepatic encephalopathy (HE). This study investigates the role of astrocyte swelling on Zn2+ homeostasis in hypoosmotically treated astrocytes by using the Zn2+ indicators Newport-Green, Zinquin, and RhodZin-3. Hypoosmolarity (205 mosmol/L) led to a persistent increase of the intracellular "free" Zn2+ concentration [Zn2+](i) within 15 min, which was reversible after reinstitution of normoosmolarity (305 mosmol/L). The hypoosmotic [Zn2+]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 79 publications
(79 reference statements)
3
51
0
Order By: Relevance
“…Hypoosmotic astrocyte swelling rapidly increases the levels of cytosolic, mitochondrial and nuclear free Zn 2þ in cultured rat astrocytes [20 ]. The increase of [Zn 2þ ] i depends on NMDA receptor activation and nNOS-catalyzed nitric oxide synthesis, but is insensitive to inhibitors of NADPH oxidase [20 ].…”
Section: Zinc Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoosmotic astrocyte swelling rapidly increases the levels of cytosolic, mitochondrial and nuclear free Zn 2þ in cultured rat astrocytes [20 ]. The increase of [Zn 2þ ] i depends on NMDA receptor activation and nNOS-catalyzed nitric oxide synthesis, but is insensitive to inhibitors of NADPH oxidase [20 ].…”
Section: Zinc Mobilizationmentioning
confidence: 99%
“…Activation and overexpression of Na-K-Cl-cotransporter 1 (NKCC1) are involved in the swelling response [18,19 ]. Activation of NADPH oxidase isoforms in response to hypoosmotic astrocyte swelling or ammonia exposure is the major source of the early ROS formation [12], whereas Ca 2þ /calmodulin-dependent isoforms of nitric oxide synthase are involved in the swelling-induced nitric oxide synthesis [11,20 ].…”
Section: Ammonia and Astrocyte Swelling Induce Oxidative Stressmentioning
confidence: 99%
“…A crucial role in MHC-II, EPO, MT, and GS production seems to be played by zinc, a transition metal that is capable of stimulating EPO and MT production [87][88][89][90]. Furthermore, zinc ions have been shown to induce the dimerization of class II MHC molecules, increasing their activity [88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Together with this morphological change, the astrocytic functionality, by which cellular signaling mediated by neuro-/glio-transmitters and degradation of glycogen as the main energy reserve in the brain are tightly regulated, is also altered. [18][19][20][21][22] ATP is a cellular energy source and also plays a critical role as a neuro-/glio-transmitter, 28) and thus the functionality of its receptors involved in the cellular signaling might be different between in vitro cultured and in vivo tissue astrocytes. In this study, however, we demonstrated that in vivo tissue astrocytes express constitutively activated P2X7Rs the same as in vitro cultured ones do.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] When astrocytes are activated under pathological conditions, they exhibit different functionalities such as neuro-/glio-transmitter clearance systems. [18][19][20][21][22] These findings may imply the possibility that there are differences in the functional expression of P2X7Rs between in vitro cultured and in vivo tissue astrocytes. Brain acute slice cultures are a widely accepted in vitro experimental system that reflects in vivo cell conditions better than in vitro cell culture ones.…”
mentioning
confidence: 99%